P1-S6.29 Longitudinal trends in HIV testing and prevalence among STI clinic patients in Lilongwe, Malawi: 2006–2010. (10th July 2011) - Powers, K; Kamanga, G; Mapanje, C; Malava, J K; Chindebvu, M; Kamzati, H; Martinson, F; Miller, W; Cohen, M; Hoffman, I
Abstract : Background: To understand longitudinal trends in HIV status awareness, HIV test acceptance, and HIV prevalence among patients of a sexually transmitted infections (STI) clinic in Lilongwe, Malawi, we conducted descriptive analyses of these endpoints over the last 5 years. Methods: Using data collected routinely at all STI clinic visits since March 2006, we calculated the proportion of visits in each of the last five calendar years (2006, 2007, 2008, 2009, and 2010) during which patients reported a previous HIV test, and among those, the proportions reporting positive and negative results. We also calculated the proportion accepting HIV tests at the clinic, and among those who received HIV tests at their visits, the proportion who had positive results. We conducted log-binomial regression with generalised estimating equations to analyse trends in each endpoint over time. Results: An average of 8944 clinic visits occurred each year, approximately 60% by females and 40% by males. The proportion of visits at which patients reported a previous HIV test increased from 57% in 2006 to 86% in 2010 (p<0.0001) (Abstract P1-S6.29 figure 1 ). Among those reporting a previous test, the proportions reporting negative or positive results remained relatively constant, at approximately 70% and 30%, respectively (results not shown). At visits where patients did not report a prior positive HIV test, the proportion accepting HIV antibody tests increased from 50% to 78% (p<0.0001). Among all those who received HIV antibody tests at a visit, the proportion who were found to be HIV-positive decreased from 31% to 17% (p<0.0001), with a decrease from 13% to 10% among those reporting a previous negative test (p<0.0001) (Abstract P1-S6.29 figure 1 ). Conclusions: Over the last 5 years, the proportion of STI clinic visits at which patients reported awareness of their HIV status has increased, including an increase in known positives to 25% of all patients. At visits where patients did not report a previous positive result, the proportion who accepted rapid antibody tests has also increased. Among those receiving HIV tests at their clinic visits, the proportion testing HIV-positive has decreased substantially, although 10% of those with a previous negative result tested positive. These findings raise great concern about ongoing HIV acquisition and transmission in patients becoming aware of their serostatus through expanded HIV testing. Novel and better HIV prevention strategies for these patients are urgently needed.